2015
DOI: 10.5530/ijper.49.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of learning style preferences of pharmacy students: Findings from public university of Malaysia

Abstract: Background: Student's learning style preference is an important consideration for effective and high quality teaching and learning process. Different teaching approaches may not suit students' preferences, hence, producing a gap between learning and delivery instructions. The aim of this study was to assess the learning style preferences among the first year pharmacy students of public sector university of Malaysia. Methods: A prospective cross sectional study was conducted during non-lecture hour using valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…6 To date, two studies have been conducted to determining the learning style preferences of undergraduate pharmacy students in Malaysia. 2,7 However, none of these studies used the Pharmacists' Inventory of Learning Style (PILS) tool, which was specifically developed and validated for pharmacy education. 8,9 PILS divided the learning styles of pharmacists into four groups: accommodator, assimilator, converger and diverger.…”
Section: Introductionmentioning
confidence: 99%
“…6 To date, two studies have been conducted to determining the learning style preferences of undergraduate pharmacy students in Malaysia. 2,7 However, none of these studies used the Pharmacists' Inventory of Learning Style (PILS) tool, which was specifically developed and validated for pharmacy education. 8,9 PILS divided the learning styles of pharmacists into four groups: accommodator, assimilator, converger and diverger.…”
Section: Introductionmentioning
confidence: 99%
“…In (Milicevic et al, 2011;Al-Saud, 2013;Elkalmi et al, 2015;Gurpinar et al, 2010;O'Mahony et al, 2016), they used the higher data set in order to reach accurate results. Milicevic et al (2011), introduced proposed recommendation module "Protus" which assist learners for programming tutoring system during determining learners' knowledge level and their interests automatically.…”
Section: Related Workmentioning
confidence: 99%
“…Al-Saud (2013), aimed to investigate three factors which included learning style preferences, gender and previous academic performance of students to improve students 'performance. Elkalmi et al (2015), aimed to enhance learning experiences and improve the quality teaching for pharmacy students at Malaysia University during integration between teaching styles and students' preference in learning styles. Gurpinar et al (2010), aimed to determine the suitable learning styles of medical students during measuring satisfaction factor for various education methods and academic achievement in them.…”
Section: Related Workmentioning
confidence: 99%
“…31 Elkalmi et al used a VAK scale on pharmacy students, and reported a high majority of students to prefer the visual form of learning. 12 Skeptics suggest that while students may have a 'preference' for one form of learning, they have the ability to learn from all different mediums of instruction. 32 Regardless of the learning index used or results reported, there is growing agreement that teaching to a single learning style may not be best suited for all students, which has led to a call for diversity in instructional design in the classroom.…”
Section: Multimodal Teaching To Address Multiple Learning Stylesmentioning
confidence: 99%
“…7 While the survey does not suggest hard and fast boundaries, it classifies visual learners to prefer diagrams, graphs and charts; aural learners to prefer lectures recordings, discussions, and seminars; reader/writer learners to prefer books, handouts, slides and notes; and kinesthetic learners to prefer real-life examples, models, demonstrations and physical activity. 8 Various studies have reported a wide range of learning styles within different cohorts of medical, dental, nursing and pharmacy students [9][10][11][12] and have found a significant number of students preferring a multimodal form of learning, which combines two or more learning preferences. These studies have implicated that redesigning traditional lectures to include additional teaching tools, which can target a larger variety of learning styles, can strengthen learning for students.…”
Section: Introductionmentioning
confidence: 99%